Implementation of a National 5-Year Plan for Prehospital Emergency Care in Singapore and Impact on Out-of-Hospital Cardiac Arrest Outcomes From 2011 to 2016 - Ho, Andrew Fu Wah (WILEY, 2022)
10.1161/JAHA.119.015368